Design of low power wideband low noise amplifier for software defined radio at 100 MHz to 1 GHz - Azahari, Salleh; Yong, K. S.; Mohamad Zoinol Abidin, Abd Aziz; Mohamad Harris, Misran; N. R., Mohamad (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.